2021
DOI: 10.5935/1415.2762.20210059
|View full text |Cite
|
Sign up to set email alerts
|

Estratégias Educativas De Ressuscitação Cardiopulmonar Para Leigos: Revisão Integrativa Da Literatura

Abstract: RESUMO Objetivo: identificar as estratégias de ensino e aprendizagem da ressuscitação cardiopulmonar voltadas para pessoas leigas. Método: revisão integrativa realizada nas fontes National Library of Medicine; National Institutes of Health; Cumulative Index to Nursing and Allied Health Literature; Literatura Latino-Americana e do Caribe em Ciências da Saúde; Web of Science; e SCOPUS. Resultados: identificaram-se 932 estudos e incluíram-se 11. As estratégias foram: aula expositiva; treinamento com manequim/inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
(65 reference statements)
0
4
0
3
Order By: Relevance
“…It is worth mentioning that the Content Validity Indexes among judges were ≥ 0.90, similar to the present investigation. It reinforces that videos are excellent strategies for training lay people (17) , but they need methodological rigor in their production (18) .…”
Section: Elaboration Of An Educational Video For Cardiopulmonary Resu...mentioning
confidence: 75%
“…It is worth mentioning that the Content Validity Indexes among judges were ≥ 0.90, similar to the present investigation. It reinforces that videos are excellent strategies for training lay people (17) , but they need methodological rigor in their production (18) .…”
Section: Elaboration Of An Educational Video For Cardiopulmonary Resu...mentioning
confidence: 75%
“…However, not delimiting the concept of technology would make the scope of the review unfeasible, due to the possibility of covering management and assistance technologies that include, for example, relationships such as bonding, empowerment and reception. Thus, studies that expose educational strategies but do not mention educational technologies will also be excluded, since these strategies have already been well delimited by the current literature (5) .…”
Section: Conceptmentioning
confidence: 99%
“…An integrative review research identified the teaching and learning strategies of cardiopulmonary resuscitation aimed at lay people. However, there was no mapping of educational technologies undertaken in the educational process (5). Among the gaps that need to be explored, there is the lack of knowledge of the list of the most adopted technologies and their effectiveness, theoretical references are followed, and mainly if they went through a validation process.…”
Section: Introductionmentioning
confidence: 99%
“…É válido destacar que os Índices de Validade de Conteúdo entre os juízes foram ≥ 0,90, semelhante ao da presente investigação. Reforça-se que vídeos são excelentes estratégias para o treinamento de leigos (17) , mas precisam de rigor metodológico em sua produção (18) .…”
Section: Elaboração De Vídeo Educativo Para Reanimação Cardiopulmonar...unclassified